2022
DOI: 10.1093/molbev/msac177
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Evolution against Host-directed Antiviral Agents: Buffalopox Virus Switches to Use p38-ϒ under Long-term Selective Pressure of an Inhibitor Targeting p38-α

Abstract: Host-dependency factors have increasingly been targeted to minimize antiviral drug resistance. In this study, we have demonstrated that inhibition of p38 mitogen activated protein kinase (MAPK, a cellular protein) suppresses buffalopox virus (BPXV) protein synthesis by targeting p38-MNK1-eIF4E signaling pathway. In order to provide insights into the evolution of drug resistance, we selected resistant mutants by long-term sequential passages (P; n = 60) in the presence of p38 inhibitor (SB239063). The P60-SB239… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Moreover, apoptosis assays determined by ow cytometry showed that hypoxia reduced chemosensitivity of glioma cells to TMZ, while drug tolerance induced by hypoxia was rescued by SB239063, a p38/MAPK inhibitor (Figs. 6E-H) (42). Furthermore, analysis of TCGA datasets revealed p38α (MAPK14) was upregulated in glioma samples compared to non-tumor samples (Fig.…”
Section: Hypoxia Induces Tmz Resistance In a P38α/mapk-dependent Mannermentioning
confidence: 83%
“…Moreover, apoptosis assays determined by ow cytometry showed that hypoxia reduced chemosensitivity of glioma cells to TMZ, while drug tolerance induced by hypoxia was rescued by SB239063, a p38/MAPK inhibitor (Figs. 6E-H) (42). Furthermore, analysis of TCGA datasets revealed p38α (MAPK14) was upregulated in glioma samples compared to non-tumor samples (Fig.…”
Section: Hypoxia Induces Tmz Resistance In a P38α/mapk-dependent Mannermentioning
confidence: 83%
“…In our study, hesperetin‐resistant BPXV mutants were not observed even when the virus was sequentially cultured 40 times in the presence of hesperetin. This seems to be due to the low genetic variability of the host factor (eIF4E), thereby imposing a higher genetic barrier to the generation of resistant viruses 33,36,53 …”
Section: Discussionmentioning
confidence: 99%
“…This seems to be due to the low genetic variability of the host factor (eIF4E), thereby imposing a higher genetic barrier to the generation of resistant viruses. 33,36,53 Since hesperetin can alter cell metabolism, its long-term use could eventually result in cytotoxicity. Therefore, its further validation, long-term in vivo efficacy, and clinical trials will be essential before actually introducing it from research into clinical settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a complete resistance could not be achieved. Previous study by our group on buffalopox virus suggests that virus switches to use alternate cellular factor (p38-α to p38-γ) upon long-term restricted availability of the inhibitor targeting p38-α (Chander et al, 2022).…”
Section: Discussionmentioning
confidence: 99%